The Foundation of Rome : Myth and History - Grandazzi, Alexandre (Book collections on Project MUSE., 1997)
At once a historical essay and a self-conscious meditation on the writing of history, The Foundation of Rome takes as its starting point a series of accounts of Rome's origins offered over the course of centuries. Alexandre Grandazzi places these accounts in their contemporary contexts and shows how the growing sophistication in methodology gradually changed the accepted views of the city's origins. He looks, for example, at the hypercritical philology of the nineteenth century which cast aside everything that could not be verified. He then explains how the increase in archaeological discoveries and changing archaeological techniques influenced the story of Rome's birth.Grandazzi produces a depiction of Rome's origins that is both up-to-date and provocative. His use of scientific parallels in describing changes in the ways texts were analyzed and his broad familiarity with comparative material make his synthesis particularly illuminating, and he writes with clarity, verve, and wit.